DEVELOPMENT OF DEMONSTRATION-BASED ENGLISH CORRESPONDENCE MODULES TO IMPROVE STUDENT LEARNING OUTCOMES - Dita Arila, Kevin (Nusantara Economics and Entrepreneurships Journals, 2023)
This research aims to produce the Demonstration-based English Language Correspondence module, testing the eligibility of module through validation tests, and knowing the differences in learning outcomes of experimental class students using Demonstration-based English Language Correspondence module and control classes that do not use module by using the t-test. This research is a development research carried out using the Research and Development (R & D) model by Dick and Carey that has been modified by researcher. The learning outcomes of students in field trials conducted on class X OTP 1 as a control class with an average value of 76 and X OTP 2 as the experimental class with an average value of 88. The results of data analysis using the t test show that the value of probabilities <0,05 (0,000 <0,05) which means that there are differences in the average learning outcomes between the experimental class and the control class. It can be concluded that the English Demonstration-based Correspondence module is effectively used to improve student learning outcomes. Suggestions for teachers are that they can use this module maximally as a reference in classroom learning activities, and for students to use this module as a source of learning and practicing questions, both in learning activities inside and outside class.